1999
DOI: 10.1021/jp991252t
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Exciton Relaxation Dynamics in C60 and C70 Solid

Abstract: The exciton dynamics of C70 solid has been investigated by the time-resolved photoluminescence (PL) and transient absorption (TA) technique and compared with the case of C60 solid. Three distinct PL bands were observed at 685, 715, and 740 nm. The high-energy band at 685 nm displayed an almost purely single-exponential decay profile, while the other two exhibited a slow-decaying tail as well, especially at low temperatures. Laser fluence dependence of PL decay profiles shows that the decay in C70 solid, in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Indeed, transient absorption studies on solid films of C 60 have shown that the decay curves of the excited state depend on the excitation intensity, and that the singlet exciton annihilation process is observed on a 10-ps-order time scale under excitation intensity conditions similar to those in the present experiment. 20,24,25 Recently, Clements et al reported similar results of transient absorption experiments on nC 60 dispersed in a micellar solution of Triton X-100 and water. 14 They attributed the shortened lifetime to singlet annihilation; however, they did not examine the excitation intensity dependence.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Indeed, transient absorption studies on solid films of C 60 have shown that the decay curves of the excited state depend on the excitation intensity, and that the singlet exciton annihilation process is observed on a 10-ps-order time scale under excitation intensity conditions similar to those in the present experiment. 20,24,25 Recently, Clements et al reported similar results of transient absorption experiments on nC 60 dispersed in a micellar solution of Triton X-100 and water. 14 They attributed the shortened lifetime to singlet annihilation; however, they did not examine the excitation intensity dependence.…”
mentioning
confidence: 70%
“…We measured the fluorescence spectra and decay profile of the same sample of nC 60 in water. A broad emission peak around 750 nm, similar to the fluorescence peak of a thin film, 20 was observed, and a time-correlated single-photon counting experiment revealed the fluorescence lifetime to be about 10 ps. 21 The fluorescence lifetime of nC 60 in water is significantly shorter than that of C 60 in toluene (1.2 ns).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…The similar time constants (∼10 ps) at different film thicknesses point to a common origin of the photoinduced dynamic process in C 70 . This process is slower than exciton–exciton annihilation, which features a time constant of 1 ps, but much faster than the nanosecond intersystem crossing process . The photon energy of 2.03 eV is known to excite intermolecular charge-transfer (CT) states, , leading to photocarrier generation.…”
Section: Resultsmentioning
confidence: 99%